2
$\begingroup$

I don't really know how to solve the following exercise, I need a little help:

a) Let $(X,\|\cdot \|)$ be a Banach space and $F\colon X \to X$ Lipschitz-continuous (i.e. $|F(x) - F(y)| \le L|x-y|$) with Lipschitz constant $L < 1$. Show that $G\colon X \to X$ with $G(x) = x + F(x)$ is bijective and its inverse function $G^{-1}\colon X \to X$ is Lipschitz-continuous with Lipschitz constant $\frac 1{1-L}$.

b) Use a) to show that there is a unique function $f \in C[0,1]$ for which the equation $$f(t) + \int_0^1e^{\tau+t-3}f(\tau)d\tau = 1 \quad \forall t \in [0,1]$$ holds. Determine $f$. Use the fact that $(X,\|\cdot \|_{\infty})$ is a Banach space.

In a) I think using the Banach fixed point theorem is the way to go in order to prove F is bijective. However, I don't know how to start or how to prove the Lipschitz continuity of $G^{-1}$.
For b) I don't know how to start, I'm thinking of the intermediate value theorem?

$\endgroup$
  • $\begingroup$ Isn't $X'$ in fact $X$? $\endgroup$ – Alex M. Jun 7 '16 at 13:35
  • $\begingroup$ Of course, I edited it. $\endgroup$ – lasik43 Jun 7 '16 at 13:37
  • $\begingroup$ Where is this exercise from? What book are you using? $\endgroup$ – Jack Jun 7 '16 at 14:17
  • $\begingroup$ It's from an exercise sheet we got from our University. I'm not using a specific book, just my professors script. $\endgroup$ – lasik43 Jun 7 '16 at 14:22
2
$\begingroup$
  1. The reverse triangle inequality yields $|G(x) -G(y)|\ge (1-L)|x-y|$. This gives the Lipschitz continuity of the inverse map, as soon as $G$ is shown to be surjective. For surjectivity, you are right to use the Banach fixed point theorem: the equation $x+F(x)=y$ has a solution for $x$ because the map $x\mapsto y-F(x)$ has a fixed point.

  2. The supremum norm of $\int_0^1e^{\tau+t-3}f(\tau)d\tau $ is at most $$\|f\|_\infty \int_0^1e^{\tau+1-3} d\tau = \|f\|_\infty (e^{-1}-e^{-2}) = L\|f\|_\infty$$ where $L = e^{-1}-e^{-2} <1$. This implies the existence and uniqueness of $f$, by virtue of $f$. To determine $f$, rewrite the equation as $$f(t) = 1 - e^t \int_0^1e^{\tau-3}f(\tau)d\tau $$ which says that $f$ is of the form $f(t)=1-Ce^t$. Plug this in the equation to find $C$.

$\endgroup$
  • $\begingroup$ I tried a lot now and don't know how to get C. Can you help me? $\endgroup$ – lasik43 Jun 11 '16 at 18:24
1
$\begingroup$

The following result proves (a).

Proposition. Suppose that $X$ is a Banach space, and that $f \colon X \to X$ has the form $f(x)=x+r(x)$ where $\operatorname{Lip}(r)<1$. Then $f$ is a lipeomorphism and $\operatorname{Lip}(f^{-1}) \leq (1-\operatorname{Lip}(r))^{-1}$.

Proof. Pick $u \in X$ and define $\xi_u$ by $\xi_u(x) = u-r(x)$. Thus $f(x)=u$ if and only if $\xi_u(x)=x$. Of course $\operatorname{Lip}(\xi_u)=\operatorname{Lip}(r)<1$, and therefore there is a unique fixed point $x$ of $\xi_u$. In particular, $f$ is bijective. Moreover $$ \begin{align} \|f^{-1}(u)-f^{-1}(v) \| &= \|x-y\| \\ &= \|\xi_u(x)-\xi_v(y)\| \\ &=\|(u-r(x)-(v-r(y))\| \\ &\leq \|u-v\| + \operatorname{Lip}(r) \|x-y\| \\ &\leq \|u-v\| + \operatorname{Lip}(r) \|f^{-1}(u)-f^{-1}(v)\| \end{align} $$ where $f(x)=u$ and $f(y)=v$. This proves that $$ \|f^{-1}(u)-f^{-1}(v) \| \leq \frac{1}{1-\operatorname{Lip}(r)} \|u-v\|. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.